Revolusi dan Inovasi Model Pembelajaran Pendidikan Agama Kristen Yang Efektif Dalam Perspektif Paulo Freire - Sensius Amon Karlau; Ivo Sastri Rukua (STT Pelita Dunia, 2022)
Abstract:Paulo Freire gave his ideas in the field of education, which also influenced the praxis of education at various families, stages, levels, types, and objectives, including Christian religious education. In his argument, Freire rejects the wrong and oppressive education pattern with the slogan